Heranças da branquitude em feminismos brasileiros - Lima, Élida (2020)
The thesis investigates psycho-socio-historical heritages of whiteness and coloniality that are expressed today in brazilian feminisms. It is a matter of analyzing these inheritances to brush against the grain the macro-social dimension, scrutinizing them in everyday life, especially in experiences developed between 2015 and 2019 in groups of mostly white intergenerational and interethnic cisgender feminists. This is where activists forged in the so-called historical feminism meet with feminists focused on intersectional practice. In contrast to normative historicities, the research suggests, as an anticolonial bet, the approximation of amerindianafro-trans-latin-american matrices. The research investigates and communicates in different voices: academic, critical, narrative and poetic